Pertumbuhan Bakteri E.Coli dan Bacillus Subtilis pada Media Singkong, Ubi Jalar Putih, dan Ubi Jalar Kuning Sebagai Substitusi Media NA - Ariyanti, Widya; Rahayu, Triastuti Rahayu, S.Si. M.Si (2016)
Bacteria in growth required nutrient, sources of energy and special environment conditions in growth. The media which often used in growth of bacteria was NA media. Costly NA encourage the researcher to find the media from easily material, cheap, and there was a source of nutrients for the growth of bacteria such as cassava, white and yellow fleshed sweet potatoes with high carbohydrate as a source of carbon for bacterial growth. This research was an experimental study using two factor of completely randomized design (CDR). Fist factor was a types of bacteria, such as E.coli (B1) and Bacillus subtilis (B2) and the second factor was the types of media, such as NA media (M0) white fleshed sweet potato (M1), yellow fleshed sweet potato (M2) and cassava (M3). Inoculation used streak plate method which incubated at 37°C for 24 hours. Parameters measured were bacterial growth concerned with the thickness of the lines streak, size of colony, fertility, and density in media of bacteria growth. The results showed that growth of bacteria in the media of white fleshed sweet potato was better than yellow fleshed sweet potato and cassava, but the growth of bacteria on white fleshed sweet potato was not better than NA media